Cigarette Smoke-Induced Cell Death Causes Persistent Olfactory Dysfunction in Aged Mice - Ueha, Rumi; Ueha, Satoshi; Kondo, Kenji; Kikuta, Shu; Yamasoba, Tatsuya (Frontiers in Aging Neuroscience, 2018)
Introduction: Exposure to cigarette smoke is a cause of olfactory dysfunction. We previously reported that in young mice, cigarette smoke damaged olfactory progenitors and decreased mature olfactory receptor neurons (ORNs), then, mature ORNs gradually recovered after smoking cessation. However, in aged populations, the target cells in ORNs by cigarette smoke, the underlying molecular mechanisms by which cigarette smoke impairs the regenerative ORNs, and the degree of ORN regeneration after smoking cessation remain unclear. Objectives: To explore the effects of cigarette smoke on the ORN cell system using an aged mouse model of smoking, and to investigate the extent to which smoke-induced damage to ORNs recovers following cessation of exposure to cigarette smoke in aged mice. Methods: We intranasally administered a cigarette smoke solution (CSS) to 16-month-old male mice over 24 days, then examined ORN existence, cell survival, changes of inflammatory cytokines in the olfactory epithelium (OE), and olfaction using histological analyses, gene analyses and olfactory habituation/dishabituation tests. Results: CSS administration reduced the number of mature ORNs in the OE and induced olfactory dysfunction. These changes coincided with an increase in the number of apoptotic cells and Tumor necrosis factor (TNF) expression and a decrease in Il6 expression. Notably, the reduction in mature ORNs did not recover even on day 28 after cessation of treatment with CSS, resulting in persistent olfactory dysfunction. Conclusion: In aged mice, by increasing ORN death, CSS exposure could eventually overwhelm the regenerative capacity of the OE, resulting in continued reduction in the number of mature ORNs and olfactory dysfunction.